ANALYZING THE 2021 ISRAEL-PALESTINIAN COVERAGE: A CRITICAL DISCOURSE STUDY - Degaf, Agwin; Aziza, Renavi; Anggrisia, Nur Fitria (STKIP Siliwangi, 2025)
This study explores critical discourse analysis in the context of the prolonged Israel-Palestine conflict. It examines the discourse of two prominent outlets with different geographic and cultural contexts, The Guardian and The Jakarta Post, during the May 2021 escalation. This qualitative study applies Van Dijk's (1984) three-dimensional framework, with adaptations from Van Leeuwen (2008), to analyze news articles at macro, super, and micro levels. The findings reveal that The Guardian emphasized humanitarian impacts and used euphemistic terms, while The Jakarta Post highlighted reactive actions and employed a more direct tone. At the superstructure level, differences in story organization and headline framing were evident, with The Guardian focusing on chronological sequencing and The Jakarta Post emphasizing Indonesia’s advocacy for Palestine. At the microstructure level, The Guardian framed Israel’s actions neutrally, while The Jakarta Post reflected a pro-Palestinian stance through dysphemistic lexical choices. Ideologically, The Guardian leaned toward a neutral stance, often legitimizing Israeli actions, whereas The Jakarta Post highlighted solidarity with Palestinian victims in alignment with Indonesia’s cultural and political context. These findings highlight geographic and cultural influences on media narratives. This study fosters deeper conflict analysis, enhancing critical discourse and offering insights into the ideological underpinnings of international media coverage.